Neonatal Kidney Dimensions and Medullary Pyramid Thicknesses According to the Weight, Length and Body Mass Index of Newborns - Hatice Ayça Ata Korkmaz; Şebnem Kader (Journal of Pediatric Research, 2018)

(untitled)
Aim:The primary purpose of the present study was to investigate the relationship between neonatal kidney dimensions and medullary pyramid thicknesses (MPTs) according to the weight, length and body mass index (BMI) of newborns.Materials and Methods:A total of 237 [128 (54%) boys and 109 (46%) girls] consecutive term newborns in the first month of life were evaluated. Infants with an underlying renal disease, urinary symptoms, chromosomal abnormalities or low birth weight were excluded from the study. Greyscale ultrasound of neonatal kidneys was performed in standard transverse and longitudinal planes. Renal dimensions, parenchymal thickness and MPT were also evaluated and compared with neonatal age, height, weight, BMI and abdominal circumference (AC) and head circumferences (HC). Regression analyses were performed and graphs were plotted to determine the independent factors for renal parameters.Results:Statistically significant associations were noted in the renal dimensional measurements among neonatal weight (NW), neonatal length, BMI, HC and AC in the infants (p<0.0001). However, no statistically significant difference was observed between right kidney MPT and NW, HC, AC and BMI. In contrast, a statistically significant association was detected between left kidney MPT and NW, HC, AC and BMI.Conclusion:Neonatal kidney length, neonatal kidney width and renal parenchymal thickness measurements could be a useful method as an indicator of neonatal growth.